Kinetic study of adsorption process using chitosan, activated carbon, and rice husk for monoethanolamine (mea) wastewater treatment via batch process - Siti Zulaikha, Isa (2014)
In petrochemical industry, monoethanolamine (MEA) is a common solvent used as absorption medium to remove carbon dioxide (CO2) from the gaseous stream. In the absorber, the reaction between CO2 and MEA will generate some salt and increased the amount of the suspended solids in an absorber due to direct contact between gas and liquid (two fluid phases). This phenomenon can cause a sudden foaming where will decreasing the absorption efficiency, increasing amine loses, reduced quality of product gas, and the MEA sometimes is not appropriate to feed back into the stripper because of the properties deterioration and gives difficulties in optimizing the absorption processes and it has been removed as wastewater. This study had been conducted to examine the best method of treating the MEA wastewater. Adsorption method had been chosen in this treatment with here different adsorbents that are activated carbon, chitosan and rice husk. Three different variables that are adsorbent dosage, mixing time and mixing speed were varied to examine the effect of residue oil and MEA concentration. Then, the kinetic model of adsorption of residue oil had been obtained. The analysis of the oil and grease and amine concentration was followed by APHA methods. The result showed activated carbon which is showed the highest adsorption value of residue oil in absorbent dosage (32.14%), mixing time (62.32%), and mixing speed (64.29%) compared to chitosan adsorption value of residue oil in absorbent dosage (28.13%), mixing time (46.43%), and mixing speed (53.57%) and rice husk adsorption value of residue oil in absorbent dosage (21.43%), mixing time (37.71%), and mixing speed (44.64%). The MEA concentration in all adsorbent used in this study does not affected by the adsorption treatment based on three parameter that was been tested. The kinetic model of activated carbon and rice husks followed first order pseudo (normally expressed in the range of reaction only) while chitosan followed second order pseudo (obtain a two step linear relationship) and this model agree with chemisorptions being rate controlling. As conclusion, the adsorption technique using activated carbon (powder), chitosan (powder), and rice husk (powder) can be of the selected adsorbents because they do not affected with MEA concentration